Pilot scale enzymatic deinking of mixed office wastepaper and old newspaper - C.K.Lee; Darah Ibrahim; Ibrahim Che Omar; Wan Daud Wan Rosli (2011)
The performance of a newly developed pilot scale continuous enzymatic deinking system has been evaluated using a mixture of cellulase and xylanase enzymes in the deinking of mixed office wastepaper (MOW) and old newspaper (ONP). Optimizations of the enzymatic deinking processes were carried out, and the optimum conditions obtained for MOW and ONP were different. The highest brightness obtained from enzymatic deinking of MOW and ONP under their respective optimum conditions were about 83.6% and 41.9%, respectively. The deinking efficiency of 6.0% and 603% were obtained by enzymatic deinking process using MOW and ONP respectively. On the other hand, the deinking efficiency of 209% and 3.5% were obtained by a chemical deinking process using MOW and ONP,respectively. The findings obtained from present work indicated that enzymes have potential to be used in deinking of MOW, which is difficult to deink by conventional chemical deinking methods.